PENGARUH FASILITAS BELAJAR, MINAT BELAJAR TERHADAP HASIL BELAJARMATA PELAJARAN EKONOMI SISWA KELAS XI IPS DI SMA NEGERI 12PEKANBARU - Marena Olyvia Olyvia; Gimin '; Hendripides ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to determine the effect of learning facilities , interest in learning on learning outcomes of economic subjects class XI SMA 12Pekanbaru . Learning outcomes are influenced by several learningfactors such asfacilities and interest in learning .Class XI students of SMAN 12 Pekanbaru has a population of 114 students . Based on the results of 54 samples taken randomly in mind that as many as 20 students ( 30 % ) having a very complete home study with a value of 74. The highest percentage of students who have interest in learning at home are very high as many as 17 students ( 30 % ) with The highest percentage of 51 .The primary data obtained through kuosioner about learning facilities at home and interest in learning at home while secondary data obtained from the study hasl documentation in SMA 12 Pekanbaru .The data has been collected by the authors then analyzed by regression analysis . Before the authors conducted a regression analysis , data normality test requirements . By using the One - Sample Kolmogorov - Smirnov Test - normal distribution of data known with indigo significance of learning facilities at home 0998 and 0.968 for the significant value of the interest in learning at home .There is a significant relationship between learning facilities at home and interest in learning at home together on learning outcomes .with a count of 12 809 f greater than t table at 3:18 . While partially on learning facility there is no significant influence on learning outcomes as t , t table ( 0529 < 2.00758 ) with a percentage of 0.9 % , but interest in learning affects the learning outcomes for t > t table ( 2,800 > 2.00758 ) with perentase of 25.2 % .. As for the influence of learning facilities and interest in learning on learning outcomes can be seen from the value of the R Square sebsar 33.4 % , while the remaining 66.6 % is influenced by other factors not examined in this study .Keywords : learning facilities , interest in learning , learning outcomes